Improving Digital Literacy for Secondary School Students at SMK Muhamadiyah 2 Cileungsi - Destiana Kumala; Ana Wijandari; Suratminingsih Suratminingsih; Rofiq Noorman Haryadi (Pasundan Community Service Development, 2023)
Improving digital literacy has become an urgent need in today's information age. The purpose of this community service is to enhance the digital literacy of secondary school students at SMK Muhamadiyah 2 Cileungsi. The methods employed in this community service encompass a series of training sessions, workshops, and seminars aimed at providing students with a better understanding of digital literacy. The results of this community service demonstrate an improvement in students' comprehension of digital literacy and their ability to effectively utilize it. In conclusion, this community service has successfully enhanced the digital literacy of secondary school students at SMK Muhamadiyah 2 Cileungsi, which will provide long-term benefits for them in facing digital challenges in the future.